Clinical Nurses: Leading Through the Complexity of Human Trafficking. Issue 3 (July 2020) - Parchment, Joy; Stinson, Allan
Abstract : The global crime of human trafficking, has nursing leaders urgently assessing, developing, and implementing various strategies to ensure the safety and well-being of human trafficked victims and their teams. The complex elements of human trafficking and the impact of associated consequences on victims and teams, coupled with needed resources to serve trafficked victims, could overwhelm any health care organization and community agencies. As the call for action surrounding this victimization grows, nurses are well-positioned to lead through the complexity. This article describes an improvement project led by clinical nurses and a nurse leader that involved interdisciplinary groups, the local nonprofit community, and state agencies. The ensuing partnership created a system-wide trauma-informed human trafficking program that identified and holistically addressed the health care needs of trafficked victims throughout the risk continuum.